ENHANCING VOCABULARY THROUGH FRAYER MODEL - Riksadianti, Deriantami (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
The researcher found that high school students have problem in mastering and remembering the English words which they find in text. This research was carried out to find the significant effect of Frayer Model in enhancing students’ vocabulary. The research was taken place in one of private Vocational High School in Garut and it was participated by second grade students. The research employed quantitative methodology by using quasi experimental design. The instrument of the research was test; pretest and post-test. The purposive sampling was used. There were 42 students who participated in the study that was consisted of two groups; experimental with 22 students and control group with 20 students. Prior treatment, a pretest was administered to find out the overview of students’ vocabulary. During the treatment, participants in experimental group were exposed to use Frayer model and in control group they used conventional method; translating word using dictionary and illustration. After the treatment, post-test was administered to see the improvement gained by the participant. The data obtained from pretest and post-test were analyzed by statistical analysis; SPSS 16.00 and manual calculation. Then, the data were analyzed by using parametric test, t test. The result of the research showed the improvement of experimental group’s post-test mean score that was 80. It was bigger than their pretest mean score that was 42.82. It is also supported by the mean gain score of experimental group that got 0.54. Therefore, there was significant effect on students’ vocabulary by using Frayer Model.